The Relationship Between Nonsuicidal Self-Injury and Family Functioning: Adolescent and Parent Perspectives - Kelada, L.; Hasking, Penelope; Melvin, G. (2016)
We explored parent and adolescent reports of family functioning, how this differed if the parent was aware that their child self-injured, and how parental awareness of self-injury was related to self-injury frequency, self-injury severity, and help seeking. Participants were 117 parent–adolescent dyads, in 23 of which the adolescent self-injured. Adolescents who self-injured reported poorer family functioning than their parents, but parents who did not know about their child's self-injury reported similar functioning to parents whose children did not self-injure. Parents were more likely to know that their child self-injured when the behavior was severe and frequent. Help-seeking was more likely when parents knew about self-injury. Family-based interventions which emphasize perspective-taking could be used to effectively treat self-injury.